Method for testing coating integrity of pre-lithiated silicon-oxygen negative electrode material through electrolyte soaking

Through the electrolyte immersion inspection method, combined with vacuum drying and glove box ventilation treatment, the problem of difficulty in accurately evaluating the coating integrity of prelithiated silicon oxygen negative electrode materials in the prior art is solved, and the accurate evaluation of material coating integrity and electrolyte penetration inhibition effect is achieved.

CN119804509AActive Publication Date: 2025-04-11CHANGSHA RES INST OF MINING & METALLURGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411811861.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-11
Estimated Expiration
2044-12-10

Smart Images

  • Figure CN119804509A_ABST
    Figure CN119804509A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of detection methods, and discloses a method for detecting the coating integrity of a pre-lithiated silicon-oxygen negative electrode material through electrolyte soaking, the pre-lithiated silicon-oxygen negative electrode material is soaked in the electrolyte, the color change of the pre-lithiated silicon-oxygen negative electrode material is observed, and the characterization test is carried out, so that whether the coating of the pre-lithiated silicon-oxygen negative electrode material is complete and compact or not is accurately evaluated. According to the method, the inhibition effect of the pre-lithiated silicon-oxygen negative electrode material on electrolyte permeation and whether the content of residual alkaline substances on the surface can influence the electrolyte can be more accurately judged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of detection methods, and in particular relates to a method for inspecting the coating integrity of a pre-lithiated silicon-oxygen negative electrode material by immersing it in an electrolyte. Background Art

[0002] With the development of the times, people's demand for high-energy-density lithium-ion batteries is increasing. The specific capacity of the widely used graphite negative electrode materials is close to its theoretical value (372mAh / g), and it is difficult to further improve it. Since silicon-oxygen negative electrode materials have relatively low expansion (150%-200%) and have a long cycle life, they are easier to achieve mass production and application. However, the presence of some oxygen elements in silicon-oxygen negative electrode materials will cause the consumption of active lithium during the first lithium insertion process, resulting in a low first coulombic efficiency. Therefore, it is of great research significance to improve the first coulombic efficiency of silicon-oxygen negative electrode materials.

[0003] At present, pre-lithiation technology is considered to be the best method to improve the first efficiency of silicon-oxygen negative electrode materials. The essence of pre-lithiation is to use lithium sources (LiH, Li2CO3, LiOH, etc.) to react with SiO2 in silicon-oxygen negative electrode materials in advance to generate lithium silicates (Li4SiO4, Li2SiO3, Li2Si2O5) to avoid the consumption of active lithium in the battery, thereby improving the first coulombic efficiency. Among them, by using LiH as a lithium source to pre-lithiate silicon-oxygen negative electrode materials, the first coulombic efficiency can reach more than 90%.

[0004] However, since the pre-lithiation silicon oxygen negative electrode material is modified with a lithium source, Li2O will remain on the surface of the carbon layer after the reaction. When exposed to the air, it will react with oxygen, water and carbon dioxide to produce Li2CO3 and LiOH, which will make the overall alkalinity of the aqueous slurry higher during the slurrying process (pH>12). Therefore, during the homogenization process of the pre-lithiation silicon oxygen negative electrode material, the alkaline solution will penetrate into the interior of the carbon layer and react with the silicon grains to produce hydrogen, resulting in a slurry gasification reaction. In addition, the alkaline substances on the surface of the pre-lithiation silicon oxygen negative electrode material will also cause the electrolyte to decompose and produce gas, thereby affecting the transmission of lithium ions and causing safety hazards. During the battery cycle, the electrolyte will also penetrate into the carbon layer and react with the silicon grains to produce Li2SiF6, causing capacity decay.

[0005] For the defects of the above-mentioned silicon oxide negative electrode materials after pre-lithiation, the current main method is to improve the coating integrity of the surface of the pre-lithiation silicon oxide negative electrode material through the back-end coating method, thereby inhibiting the gas production reaction and preventing the infiltration of alkaline solutions and electrolytes. However, there are relatively few studies on the inspection methods for the coating integrity of pre-lithiation silicon oxide negative electrode materials. Therefore, in the process of testing and screening negative electrode materials, it is particularly important to accurately evaluate the coating integrity of each material, especially for the safety of the material in subsequent battery applications and its service life. It has a very important reference significance. Patent document CN201910594116.5 discloses a method for accurately measuring the gas production of lithium-ion battery silicon negative electrode, which includes the following steps: 1) preparing the components of the slurry; 2) mixing and ball-milling the components of the slurry; 3) pre-weighing the aluminum-plastic film bag, and then weighing the mixed ball-milled slurry after being put into the aluminum-plastic film bag; 4) partially evacuating the aluminum-plastic film bag containing the slurry, the vacuum degree of the equipment is 0.01~0.02Mpa, and then sealing; 5) measuring the volume of gas generated: fixing the sealed aluminum-plastic film bag at the bottom of the container, completely immersing it in the medium measurement liquid, recording the volume density of the aluminum-plastic film bag, and recording the volume density again when gas is generated. The shortcomings of the above patent are that it is difficult to accurately evaluate the more microscopic gas production reaction, and it is impossible to accurately judge whether there is a significant inhibitory effect on the gas production of the electrolyte, and it is also impossible to judge whether the residual alkali content on the surface will affect the electrolyte. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a simple and accurate method for evaluating whether the coating of the pre-lithiated silicon oxide negative electrode material of the lithium-ion battery is complete and dense. This method can more accurately judge the inhibitory effect of the pre-lithiated silicon oxide negative electrode material on the penetration of the electrolyte, and whether the content of alkaline substances residual on the surface will affect the electrolyte.

[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for testing the coating integrity of a pre-lithiated silicon-oxygen negative electrode material by immersion in an electrolyte comprises the following steps: (1) Place the pre-lithiated silicon-oxygen anode material to be tested into a sample container and place it in a vacuum drying oven together with the experimental instruments for drying; (2) After drying, take out all items and put them into the transition chamber of the glove box for ventilation. After ventilation, place all items in the inner space of the glove box, drip the electrolyte into the pre-lithiation silicon oxide negative electrode material, soak it, stir it evenly, and take out the sample container; (3) Place the sample container in a vacuum drying oven and heat it under vacuum; (4) Take out the sample container, filter and clean the sample, vacuum dry it, and then conduct characterization test; if the electrolyte turns light yellow after immersion, and the peaks of Li2SiF6 and LiF and the generation of organic layer are found after characterization test, it indicates that the coating of the pre-lithiation silicon oxygen negative electrode material to be tested is incomplete; if there is no obvious color change before and after immersion in the electrolyte, and there is no obvious difference in the test characterization before and after immersion, it indicates that the coating of the pre-lithiation silicon oxygen negative electrode material to be tested is complete and dense.

[0008] In the above method, preferably, in step (1), the pre-lithiated silicon oxide negative electrode material to be tested is an incompletely coated pre-lithiated silicon oxide negative electrode material or a completely and densely coated pre-lithiated silicon oxide negative electrode material.

[0009] Preferably, the sample container is a glass sample bottle, and the experimental instrument includes a glass rubber-tipped dropper and a glass rod.

[0010] Preferably, in steps (1) and (4), the drying temperature is 80°C to 120°C, and the drying time is more than 4 hours. The vacuum drying is mainly to evaporate the moisture in the material and the experimental instrument to reduce the effect of moisture on the water oxygen value in the glove box. In addition, moisture can cause the hydrolysis of lithium salts and produce undesirable by-products. The dried material can avoid the effect of moisture on the electrolyte during the immersion process. Preferably, in step (2), the sample container is kept tightly covered during the process of being taken out of the drying box and placed in the transition chamber of the glove box, and all items are exposed to the air for no more than 2 minutes to prevent the entry of moisture in the air and ensure that the sample container and experimental instruments remain dry.

[0011] Preferably, in step (2), the ventilation is performed more than three times, the purpose of which is to remove oxygen from the surface of the sample container and the experimental instrument to reduce its effect on the oxidation of the electrolyte; after all items are placed in the internal space of the glove box, they are left for a period of time until the water oxygen value in the glove box is less than 0.01 ppm, and then the electrolyte is dripped into the pre-lithiation silicon oxide negative electrode material to soak.

[0012] Preferably, in step (2), the electrolyte comprises LiPF6, ethylene carbonate-diethyl carbonate-dimethyl ester cosolvent, carbonate and fluoroethylene carbonate, wherein the volume ratio of LiPF6, cosolvent and carbonate is (1.5-2.2): (0.8-1.2): (1.5-2.2), and the mass of fluoroethylene carbonate is 7-12wt% of the electrolyte. The sample container is opened and placed in the glove box for a period of time before adding the electrolyte, mainly to reduce the water oxygen value of the material through the circulation function of the glove box. The electrolyte can be added after the water oxygen value of the glove box is less than 0.01ppm. The electrolyte is mainly the electrolyte commonly used in the negative electrode material.

[0013] Preferably, in step (3), the vacuum heating temperature is 60°C to 100°C, and the vacuum heating time is 48h to 72h. The vacuum drying temperature and time should not be too high or too long. Too high a temperature and too long a time may cause the decomposition of the electrolyte and the reaction between the carbon layer and the electrolyte, resulting in excessive side reactions and affecting the judgment of the experimental results.

[0014] Preferably, in step (4), the solvent used for cleaning is carbonate. Carbonate can effectively dissolve a variety of organic matter and inorganic salts, and is suitable for cleaning the electrolyte on the surface of pre-lithiated silicon oxide negative electrode materials. Compared with other solvents, carbonate has lower toxicity, less impact on the environment and human body, and is more in line with the requirements of green chemistry. Carbonate has moderate volatility and can evaporate quickly after cleaning, avoiding residual carbonate from affecting the judgment of subsequent test results. In addition, carbonate has good chemical stability and is not prone to side reactions, which can ensure the cleaning effect of the electrolyte. Compared with other high-end solvents, the cost of carbonate is relatively moderate and suitable for large-scale application.

[0015] Preferably, in step (4), the characterization test includes any one or more of XRD, TEM, and SEM.

[0016] After testing, the electrolyte of the incompletely coated pre-lithiation silicon-oxygen negative electrode material after immersion showed a distinct light yellow color. The main reason for the change in the color of the electrolyte is that there are more Li2CO3 and LiOH remaining on the surface, which causes the electrolyte to decompose under heating conditions, thereby changing its color; and XRD can observe the obvious peak generation of Li2SiF6 and LiF, and the intensity of the Li2SiO3 diffraction peak is also significantly reduced; TEM and SEM test characterization can clearly observe the generation of a thicker organic layer. The generation of Li2SiF6 is due to the fact that the carbon layer is not densely coated after pre-lithiation, and the electrolyte easily penetrates into the interior through the carbon layer and reacts with the silicon grains (Si+2LiPF6→Li2SiF6+2PF3), so XRD can observe obvious diffraction peaks. The generation of LiF and a thicker organic layer is mainly due to the decomposition of LiPF6 and other electrolyte components caused by alkaline substances, which causes LiF and the decomposition products of the electrolyte to grow on the surface of the carbon layer, so that obvious LiF diffraction peaks and the generation of a thicker organic layer can be observed. For the modified pre-lithiation silicon negative electrode oxygen material, the electrolyte has no obvious color change, and there is no obvious difference in the test characteristics before and after immersion.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention aims to accurately evaluate whether the coating of pre-lithiation silicon oxide negative electrode materials is complete and dense, and provides a simple and accurate method for evaluating whether the coating of pre-lithiation silicon oxide negative electrode materials of lithium-ion batteries is complete and dense. This method can more accurately judge the inhibitory effect of pre-lithiation silicon oxide negative electrode materials on electrolyte penetration, and whether the alkaline substance content residual on the surface will affect the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 The experimental results of the present invention after observing the gas generation phenomenon of (a) unmodified and (b) modified pre-lithiation silicon oxygen; Figure 2 The experimental results of the unmodified, modified and blank control electrolytes after heating and immersion in Example 1 of the present invention are shown in FIG. Figure 3 The XRD diagram of the unmodified pre-lithiated silicon oxide before and after immersion in Example 1 of the present invention; Figure 4 This is a transmission electron microscope image of the surface morphology of the unmodified pre-lithiated silicon oxide after immersion in Example 1 of the present invention; Figure 5 This is a scanning electron microscope image of the surface morphology of the unmodified pre-lithiated silicon oxide after immersion in Example 1 of the present invention; Figure 6 The XRD diagram of the modified pre-lithiated silicon oxide before and after immersion in Example 1 of the present invention; Figure 7 This is a transmission electron microscope image of the surface morphology of the modified pre-lithiated silicon oxide after immersion in Example 1 of the present invention; Figure 8 This is a scanning electron microscope image of the surface morphology of the modified pre-lithiated silicon oxide after immersion in Example 1 of the present invention; Fig. 9 This is a graph showing the experimental results of the unmodified 2 and blank control 2 of Example 2 of the present invention after heating and immersion in the electrolyte; Fig.10 This is the XRD diagram of the unmodified 2 pre-lithiated silicon oxide after immersion in Example 2 of the present invention; Fig.11 The surface morphology scanning electron microscope images of the unmodified 2 pre-lithiated silicon oxide before (a) and after (b) immersion in Example 2 of the present invention are shown; Fig.12 This is a graph showing the experimental results of Example 3 of the present invention, unmodified 3, and blank control 3 after heated immersion in the electrolyte; Fig.13 This is the XRD diagram of the unmodified 3 pre-lithiated silicon oxide after immersion in Example 3 of the present invention; Fig.14 The surface morphology scanning electron microscope images of the unmodified 3 pre-lithiated silicon oxide before (a) and after (b) immersion in Example 3 of the present invention are shown; Fig.15 This is a graph showing the experimental results of the electrolyte heating and immersion of the modified 2 of Example 4 and the blank control 4 of the present invention; Fig.16 This is the XRD diagram of the modified 2 pre-lithiated silicon oxide after immersion in Example 5 of the present invention; Fig.17 These are scanning electron microscope images of the surface morphology of the modified 2 pre-lithiated silicon oxide before (a) and after (b) immersion in Example 6 of the present invention. DETAILED DESCRIPTION

[0020] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0021] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0022] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0023] The following embodiments use unmodified pre-lithiation silicon oxide negative electrode materials to simulate the coating of incomplete pre-lithiation silicon oxide negative electrode materials, and modified pre-lithiation silicon oxide negative electrode materials to simulate the coating of complete and dense pre-lithiation silicon oxide negative electrode materials. The unmodified pre-lithiation silicon oxide negative electrode material is a pre-lithiation silicon oxide negative electrode material obtained by mixing and sintering an ordinary carbon-coated silicon oxide negative electrode material with a lithium source without any post-treatment process. The modified pre-lithiation silicon oxide negative electrode material is a pre-lithiation silicon oxide negative electrode material obtained by secondary carbon coating and surface modification of the pre-lithiation silicon oxide negative electrode material by chemical vapor deposition, and the amount of residual alkali on the surface is low, and the coating is complete and dense. The specific preparation method is as follows: CMC (carboxymethyl cellulose) (solid content 1.12%), SP (carbon black), sample (pre-lithiation silicon material before and after modification), graphite, SBR (styrene-butadiene rubber) (solid content 40%) were added to the mixing cup in turn, and then stirred with a vacuum degassing mixer. After stirring, 10g of the slurry was weighed, put into a vacuum plastic bag, and vacuum sealed with a sealing machine. Finally, the vacuum plastic bag was placed in a constant temperature environment of 25°C to observe the gas generation phenomenon. The comparison of the gas generation evaluation test results of the unmodified and modified pre-physicalized silicon materials is shown in Table 1. Figure 1 .

[0024] Table 1: Unmodified and modified pre-lithiation silicon oxide anode materials - gas production evaluation experiment

[0025] From Table 1, Figure 1 It can be seen that the unmodified pre-lithiated silicon oxide negative electrode material can be used to simulate the incomplete pre-lithiated silicon oxide negative electrode material coated in the following embodiments, and the modified pre-lithiated silicon oxide negative electrode material can be used to simulate the complete and dense pre-lithiated silicon oxide negative electrode material coated in the following embodiments.

[0026] Embodiment 1: A method for testing the coating integrity of a pre-lithiated silicon-oxygen negative electrode material by immersion in an electrolyte comprises the following steps: (1) Prepare the unmodified and modified pre-lithiated silicon-oxygen anode materials prepared above and experimental instruments such as a glass rubber-tipped dropper and a glass rod; (2) Weigh 2g of each material and put it into a glass sample bottle, and then put the experimental instruments (glass rubber-tipped dropper, glass rod) into a vacuum drying oven for drying at 80℃ for more than 4h; (3) Take out all items, quickly cover the glass sample bottle, and then quickly put it into the transition chamber of the glove box for at least three times of ventilation; in the glove box, open the glass sample bottle and leave it for a while until the water oxygen value in the glove box is less than 0.01ppm; then drop the electrolyte into the glass sample bottle, stir it with a glass rod until it becomes a slurry, cover the bottle cap, and take out the glass sample bottle; the components of the electrolyte specifically include: 1M LiPF6, a co-solvent of ethylene carbonate (EC)-diethyl carbonate (DEC)-dimethyl ester, carbonate (volume ratio: LiPF6: co-solvent: carbonate = 2:1:2) and fluoroethylene carbonate (FEC) (accounting for 10 wt% of the entire electrolyte); (4) Place the glass sample bottle in a vacuum drying oven and heat it under vacuum at 60°C for 48 hours; (5) Take out the sample bottle, filter it first, and then wash it three times with carbonate; vacuum dry it at 80℃ for more than 4h, and take out the sample for XRD, TEM, SEM and other characterization tests. For the unmodified pre-lithiation silicon oxide negative electrode material, the electrolyte after immersion is obviously light yellow, and XRD can observe the obvious peak generation of Li2SiF6 and LiF. TEM and SEM test characterization can clearly observe the generation of a thicker organic layer. For the fully coated pre-lithiation silicon oxide negative electrode material, the electrolyte has no obvious color change, and there is no obvious difference in the test characterization before and after immersion. There is no obvious difference in the XRD, SEM, and TEM characterization of the pre-lithiation silicon oxide negative electrode material before and after immersion.

[0027] The experimental comparison of unmodified, modified and blank control electrolytes after heating and immersion is shown in Table 2-Table 4. Figure 2-Figure 8 .

[0028] Table 2: Pre-lithiation silicon-oxygen anode materials (unmodified)

[0029] Table 3: Pre-lithiation silicon-oxygen anode materials (after modification)

[0030] Table 4: Blank control

[0031] From Table 2 to Table 4, Figure 2-Figure 8 It can be seen that: compared with the unmodified ones, the color of the modified ones after immersion in the electrolyte has no obvious change, the results of the XRD test are not significantly different from those before immersion, and the TEM and SEM test results show that no obvious organic layer appears. Compared with the unmodified ones, the blank control has no obvious color change after immersion in the electrolyte, indicating that the decomposition of the electrolyte will not occur under the heating conditions of this temperature and time. This method can more accurately determine the inhibitory effect of the pre-lithiation silicon oxide negative electrode material on the penetration of the electrolyte, and whether the residual alkaline content on the surface will affect the electrolyte.

[0032] Embodiment 2: A method for testing the coating integrity of a pre-lithiated silicon-oxygen negative electrode material by immersion in an electrolyte comprises the following steps: (1) Prepare pre-lithiation silicon-oxygen anode material (unmodified 2) and experimental instruments such as glass rubber-tipped dropper and glass rod; (2) Weigh 2g of each material and put it into a glass sample bottle, and then put the experimental instruments (glass rubber-tipped dropper, glass rod) into a vacuum drying oven for drying at 80℃ for more than 4h; (3) Take out all items, quickly cover the glass sample bottle, and then quickly put it into the transition chamber of the glove box for at least three times of ventilation; in the glove box, open the glass sample bottle and leave it for a while until the water oxygen value in the glove box is less than 0.01ppm; then drop the electrolyte into the glass sample bottle, stir it with a glass rod until it becomes a slurry, cover the bottle cap, and take out the glass sample bottle; the components of the electrolyte specifically include: 1M LiPF6, a co-solvent of ethylene carbonate (EC)-diethyl carbonate (DEC)-dimethyl ester, carbonate (volume ratio: LiPF6: co-solvent: carbonate = 2:1:2) and fluoroethylene carbonate (FEC) (accounting for 10 wt% of the entire electrolyte); (4) Place the glass sample bottle in a vacuum drying oven and heat it under vacuum at 40°C for 24 hours; (5) Take out the sample bottle, filter it first, and then wash it three times with carbonate; vacuum dry it at 80°C for more than 4 hours, and take out the sample for characterization tests such as XRD, TEM, and SEM.

[0033] Table 5: Pre-lithiation silicon oxide negative electrode materials (unmodified 2)

[0034] Table 6: Blank Control 2

[0035] From Table 5-Table 6, Figure 9-11 It can be seen that lowering the heating temperature and reducing the heating time can significantly slow down the decomposition and deposition of the electrolyte.

[0036] Embodiment 3: A method for testing the coating integrity of a pre-lithiated silicon-oxygen negative electrode material by immersion in an electrolyte comprises the following steps: (1) Prepare pre-lithiation silicon-oxygen anode material (unmodified 3) and experimental instruments such as glass rubber-tipped dropper and glass rod; (2) Weigh 3g of each material and put it into a glass sample bottle, and then put the experimental instruments (glass rubber-tipped dropper, glass rod) into a vacuum drying oven for drying at 80℃ for more than 4h; (3) Take out all items, quickly cover the glass sample bottle, and then quickly put it into the transition chamber of the glove box for at least three times of ventilation; in the glove box, open the glass sample bottle and leave it for a while until the water oxygen value in the glove box is less than 0.01ppm; then drop the electrolyte into the glass sample bottle, stir it with a glass rod until it becomes a slurry, cover the bottle cap, and take out the glass sample bottle; the components of the electrolyte specifically include: 1M LiPF6, a co-solvent of ethylene carbonate (EC)-diethyl carbonate (DEC)-dimethyl ester, carbonate (volume ratio: LiPF6: co-solvent: carbonate = 2:1:2) and fluoroethylene carbonate (FEC) (accounting for 10 wt% of the entire electrolyte); (4) Place the glass sample bottle in a vacuum drying oven and heat it under vacuum at 60°C for 72 hours; (5) Take out the sample bottle, filter it first, and then wash it three times with carbonate; vacuum dry it at 80℃ for more than 4h, take out the sample for XRD, TEM, SEM and other characterization tests.

[0037] Table 7: Pre-lithiation silicon oxide negative electrode materials (unmodified 3)

[0038] Table 8: Blank Control 3

[0039] From Table 7-Table 8, Figure 12-14 It can be seen that extending the heating time and increasing the mass of the soaked material can significantly accelerate the decomposition and deposition of the electrolyte.

[0040] Embodiment 4: A method for testing the coating integrity of a pre-lithiated silicon-oxygen negative electrode material by immersion in an electrolyte comprises the following steps: (1) Prepare pre-lithiation silicon-oxygen anode material (modification 2) and experimental instruments such as glass rubber-tipped dropper and glass rod; (2) Weigh 2g of each material and put it into a glass sample bottle, and then put the experimental instruments (glass rubber-tipped dropper, glass rod) into a vacuum drying oven for drying at 80℃ for more than 4h; (3) Take out all items, quickly cover the glass sample bottle, and then quickly put it into the transition chamber of the glove box for at least three times of ventilation; in the glove box, open the glass sample bottle and leave it for a while until the water oxygen value in the glove box is less than 0.01ppm; then drop the electrolyte into the glass sample bottle, stir it with a glass rod until it becomes a slurry, cover the bottle cap, and take out the glass sample bottle; the components of the electrolyte specifically include: the main component is 1M LiPF6, and a co-solvent of ethylene carbonate (EC)-diethyl carbonate (DEC)-dimethyl ester, carbonate (volume ratio = 2:1:2) and 10 wt% fluoroethylene carbonate (FEC); (4) Place the glass sample bottle in a vacuum drying oven and heat it under vacuum at 70°C for 72 hours; (5) Take out the sample bottle, filter it first, and then wash it three times with carbonate; vacuum dry it at 80℃ for more than 4h, take out the sample for XRD, TEM, SEM and other characterization tests.

[0041] Table 9: Pre-lithiation silicon oxide negative electrode materials (modification 2)

[0042] Table 10: Blank Control 4

[0043] From Table 9-Table 10, Figure 15-17 It can be seen that for the pre-lithiated silicon-oxygen material that is completely and densely coated, within the above-mentioned condition parameters, even if the heating temperature is increased and the heating time is prolonged, the side reaction of the electrolyte cannot be promoted.

[0044] In summary, the method of the present invention can more accurately determine the inhibitory effect of the pre-lithiation silicon oxide negative electrode material on the electrolyte penetration, and whether the alkaline substance content remaining on the surface will affect the electrolyte.

Claims

1. A method for testing the coating integrity of pre-lithiated silicon oxide negative electrode materials by immersion in an electrolyte, characterized in that: The following steps are involved: (1) Place the pre-lithiated silicon-oxygen anode material to be tested into a sample container and place it in a vacuum drying oven together with the experimental instruments for drying; (2) After drying, take out all items and put them into the transition chamber of the glove box for ventilation. After ventilation, place all items in the inner space of the glove box, drip the electrolyte into the pre-lithiation silicon oxide negative electrode material, soak it, stir it evenly, and take out the sample container; (3) Place the sample container in a vacuum drying oven and heat it under vacuum; (4) Take out the sample container, filter and clean the sample, vacuum dry it, and then perform characterization test; if the electrolyte turns light yellow after immersion, and the peaks of Li2SiF6 and LiF and the generation of organic layer are found after characterization test, it indicates that the coating of the pre-lithiation silicon-oxygen negative electrode material to be tested is incomplete; If there is no obvious color change before and after immersion in the electrolyte, and there is no obvious difference in the test characteristics before and after immersion, it means that the pre-lithiation silicon oxide negative electrode material to be tested is completely and densely coated.

2. The method according to claim 1, characterized in that In step (1), the pre-lithiation silicon oxide negative electrode material to be tested is an incompletely coated pre-lithiation silicon oxide negative electrode material or a completely and densely coated pre-lithiation silicon oxide negative electrode material.

3. The method according to claim 1, characterized in that: In step (1), the sample container is a glass sample bottle, and the experimental instrument includes a glass rubber-tipped dropper and a glass rod.

4. The method according to claim 1, characterized in that: In steps (1) and (4), the drying temperature is 80°C to 120°C, and the drying time is more than 4 hours.

5. The method according to claim 1, characterized in that In step (2), the sample container is kept tightly covered during the process of being taken out of the drying box and placed in the transition chamber of the glove box, and all items are exposed to the air for no more than 2 minutes.

6. The method according to claim 1, characterized in that In step (2), the ventilation is performed more than 3 times; after placing all items in the inner space of the glove box, the glove box is left for a period of time until the water oxygen value in the glove box is less than 0.01 ppm, and then the electrolyte is dripped into the pre-lithiation silicon oxide negative electrode material to soak.

7. The method according to claim 1, characterized in that In step (2), the electrolyte includes LiPF6, ethylene carbonate-diethyl carbonate-dimethyl ester co-solvent, carbonate and fluoroethylene carbonate, wherein the volume ratio of LiPF6, co-solvent and carbonate is (1.5~2.2):(0.8~1.2):(1.5~2.2), and the mass of fluoroethylene carbonate is 7-12wt% of the electrolyte.

8. The method according to claim 1, characterized in that In step (3), the vacuum heating temperature is 60°C to 100°C, and the vacuum heating time is 48h to 72h.

9. The method according to claim 1, characterized in that: In step (4), the solvent used for cleaning is carbonate.

10. The method according to claim 1, characterized in that In step (4), the characterization test includes any one or more of XRD, TEM, and SEM.

Citation Information

Patent Citations

  • Method for testing carbon coating integrity of silicon-based material

    CN117589918A

  • Method and device for comparing coating integrity of positive electrode active material

    CN117969742A

  • Self healing anti corrosive coatings and a process for the preparation thereof

    US20150184304A1

  • Method for measuring pre-lithiation quantity and pre-lithiation capacity of pre-lithiation battery

    WO2023050770A1